Simplifying
3a + 2b + c = 26
Solving
3a + 2b + c = 26
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-2b' to each side of the equation.
3a + 2b + -2b + c = 26 + -2b
Combine like terms: 2b + -2b = 0
3a + 0 + c = 26 + -2b
3a + c = 26 + -2b
Add '-1c' to each side of the equation.
3a + c + -1c = 26 + -2b + -1c
Combine like terms: c + -1c = 0
3a + 0 = 26 + -2b + -1c
3a = 26 + -2b + -1c
Divide each side by '3'.
a = 8.666666667 + -0.6666666667b + -0.3333333333c
Simplifying
a = 8.666666667 + -0.6666666667b + -0.3333333333c
Answer:
inches
Step-by-step explanation:
a^2+b^2=c^2
10^2+20^2=c^2
100+400=c^2
c^2=500
CAC can be changed into CAAC. This is because the first rule says that any letter can change into an A so
CAC=CAA
The last condition says that when you double , you have to double all letters,
Since A has been doubled,C needs to be doubled too.So:
CAA=CAAC
The answer is -4 because -4^7=-16384